Accounting for non-accountants - Horner, David (New York : Kogan Page Inc, 2020)
"Accounting for Non-Accountants guides non-specialists through the fundamental principles of accounting and finance. This book presents key, and often complex, concepts in a simple and understandable way designed to be accessible to those with little or no background in accounting. Now in its 12th edition, Accounting for Non-Accountants addresses the current issues in accounting and finance, including recent, important economic issues, and provides a range of examples to understand and recognize these concepts in practice. This book has been fully updated to the latest regulatory requirements including UK GAAP accounting standards, International Financial Reporting Standards (IFRS) and International Accounting Standards (IAS). Updates also include introductions to areas including tax, transfer pricing and creative accounting. A clear and intuitive structure helps readers navigate these topics while online resources further support readers with their learning throughout. This is the guide for non-specialists to understanding how to interpret financial data and make informed decisions"--
Revised edition of the author's Accounting for non-accountants, [2017]
Includes index.
Keywords: Accounting -- Great Britain